Sexual Minority Health: A Bibliography and Preliminary Study of the Book Literature - Weiner, Sharon A. (Medical reference services quarterly, 2017)
The literature on health in people who identify as sexual minorities is scattered in many types of resources and disciplines. To help address the need for relevant, well-organized information for lesbian, gay, bisexual, and transgender people and health care providers, this study first identified books published in a ten-year period and then examined the topics, the number of books published per year, most prolific authors, and primary publishers. A wide range of publishers published a relatively small number of books (521). Most were about mental health or relationships and 24% were personal accounts. There were many subject deficiencies in the published book corpus.